2020
DOI: 10.1111/jgh.15330
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of drug and endoscopic treatment of Crohn's disease strictures: A systematic review

Abstract: Background and Aims Strictures are the commonest complication in Crohn's disease. Surgery and endoscopic dilation are the mainstays of treatment, while drug therapy has often been considered contraindicated. The benefit of nonsurgical treatments, particularly drug and endoscopic therapy, need to be defined. Methods Ovid MEDLINE, Embase, Emcare, PsycINFO, CINAHL and the Cochrane Library (inception until August 30, 2019) were searched. Studies with ≥ 10 patients with Crohn's disease strictures, reporting on outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…Despite the huge progress in the implementation of novel therapeutic agents into clinical practice, it was demonstrated that they do not influence the occurrence of fibrosis. In a recently published systematic review on nonsurgical therapy of CD-related strictures from among drug therapy only, anti-TNFα agents appeared to be effective in preventing surgery as during 4 years of follow-up, 50% of patients could escape operation [ 37 ]. Unfortunately, antifibrotic therapy is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the huge progress in the implementation of novel therapeutic agents into clinical practice, it was demonstrated that they do not influence the occurrence of fibrosis. In a recently published systematic review on nonsurgical therapy of CD-related strictures from among drug therapy only, anti-TNFα agents appeared to be effective in preventing surgery as during 4 years of follow-up, 50% of patients could escape operation [ 37 ]. Unfortunately, antifibrotic therapy is not available.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of the combination of anti‐TNF therapy and endoscopic treatment or surgery are still conflicting. Several studies have found that anti‐TNF agents applied before or after endoscopic balloon dilatation (EBD) contribute to a lower risk of bowel surgery and intestinal stricture recurrence 75‐77 . In contrast, a comparative pilot study has demonstrated that there is an increased risk of fibrosis in patients who undergo preoperative anti‐TNF‐α treatment 78 .…”
Section: Treatmentmentioning
confidence: 99%
“…Obstructive symptoms such as postprandial pain, early satiety, nausea, and vomiting are reliable clinical predictors of need for surgery in stricturing CD. 1 Unfortunately, the latter are common symptoms in pregnancy, with nausea and vomiting of pregnancy (NVP) and pregnancy-related constipation affecting up to 80% and 35% of women respectively. 3 Furthermore, abdominal examination is of limited sensitivity due to displacement of abdominal structures by the gravid uterus.…”
Section: Casementioning
confidence: 99%
“…2 Evidence supporting corticosteroid use for symptomatic strictures is limited, even in nonpregnant CD patients. 1 Approximately two-thirds of hospitalized nonpregnant patients treated with corticosteroids for symptomatic stricturing CD progress to surgical intervention during their index admission. 1 If prednisolone response is suboptimal, symptoms flare on steroid wean ,or repeated courses are required, immediate escalation to anti-TNF treatment is recommended.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation